A scoping review on the operationalization of intersectional health research methods in studies related to the COVID-19 pandemic - Adedoyin Olanlesi-Aliu; Mia Tulli; Janet Kemei; Glenda Bonifacio; Linda C. Reif; Valentina Cardo; Hannah Roche; Natasha Hurley; Bukola Salami (International Journal of Qualitative Studies on Health & Well-Being)
Purpose The COVID-19 pandemic began in early 2020 and became a global health crisis with devastating impacts. This scoping review maps the key findings of research about the pandemic that has operationalized intersectional research methods around the world. It also tracks how these studies have engaged with methodological tenets of oppression, comparison, relationality, complexity, and deconstruction. Methods Our search resulted in 14,487 articles, 5164 of which were duplicates, and 9297 studies that did not meet the inclusion criteria were excluded. In total, 14 articles were included in this review. We used thematic analysis to analyse themes within this work and Misra et al. (2021) intersectional research framework to analyse the uptake of intersectional methods within such studies. Results The research related to the COVID-19 pandemic globally is paying attention to issues around the financial impacts of the pandemic, discrimination, gendered impacts, impacts of and on social ties, and implications for mental health. We also found strong uptake of centring research in the context of oppression, but less attention is being paid to comparison, relationality, complexity, and deconstruction. Conclusions Our findings show the importance of intersectional research within public health policy formation, as well as room for greater rigour in the use of intersectional methods.